The Italian Euromelanoma Day: evaluation of results and implications for future prevention campaigns. (11th December 2012) - Suppa, Mariano; Altomare, Gianfranco; Cannavò, Serafinella P.; Capizzi, Rodolfo; Catricalà, Caterina; Colombo, Enrico; Fargnoli, Maria C.; Fossati, Barbara; Frascione, Pasquale; Lisi, Paolo; Santini, Marcello; Scalvenzi, Massimiliano; et al.
Abstract Background Melanoma incidence/mortality is increasing worldwide. "Euromelanoma Day" is a pan‐European campaign for skin cancer prevention. Results of the 2010 Euromelanoma Day in Italy are reported herein. Materials and methods A questionnaire was used to collect data on participants' characteristics and suspected skin cancers. Result A total of 1085 participants was screened (64.1% females, median age 44 years). Suspicion rate, detection rate, and positive predictive values for melanoma were 1.3, 0.28 and 21.4%, respectively. Poorly educated, ≥35 years old, pale‐skinned males were at higher risk for skin cancer than highly educated, <35 years old, darker‐skinned females, although the latter groups reported sun‐seeking behaviors. Full skin examination and dermoscopy were performed in 85.5 and 79.2% of participants. Conclusions The 2010 Italian Euromelanoma Day produced good results in terms of melanoma detection/suspicion rates, likely due to the extensive use of full clinical and dermoscopic examinations. The campaign failed to attract many high‐risk individuals. Targeted communication strategies are needed to this regard.